Analysis of Trends in Harvested Area, Production, and Productivity of Corn Commodities in Indonesia - Asriani, Asriani; Herdhiansyah, Dhian; Embe, Wa; Aksara, LM Fid; Nurcayah, Nurcayah (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
Corn is a food crop that has a strategic role in the national economy because of its role as a food ingredient, the main raw material for feed, and industrial raw materials. This research aims to analyze trends in harvest area, production, and productivity of corn commodities in Indonesia. The data used in this research is secondary data or time-series data from the Central Statistics Agency for 1981-2020. Data analysis used trend analysis. The research results show that the development of the national corn commodity in the 1981-2020 period experienced fluctuations with the corn commodity harvest area averaging 2.64% per year. National corn commodity production averages 5.90% per year. Meanwhile, for the 2010-2020 period, corn commodity production experienced an average growth of 3.77%. and in 2019 there was an increase of 30.69 million tons, which was the highest production over forty years. Meanwhile, the development of corn commodity productivity averaged 3.11% per year. During this period, national corn commodity productivity increased from 1.53 tonnes/ha in 1981 to 4.84 tonnes/ha in 2020.